Dziedzictwo kulturowe łódzkich Żydów i jego rola w rozwoju współczesnej Łodzi i regionu łódzkiego - Cudny, Waldemar; Kubiak, Ewa; Rouba, Rafał (Przegląd Nauk Historycznych, 2011)
This article presents the key elements of the material and non-material heritage created by Łódź Jews. Those heritage elements play an extremely important part in shaping the contemporaneity of Łódź and the entire region. They are part of the cultural heritage of the city and its inhabitants. At every step in Łódź, we meet the houses, factories, palaces, hospitals, memorials and museum collections relating to the Łódź Jews. This opportunity to familiarize with the history of the Jewish people once lived in Łódź is very important for local residents and tourists. The presentation of Jewish culture, is also used to fight negative stereotypes and the phenomena of xenophobia and anti-Semitism in Łódź and the region.